A review on supercapacitors based on plasma enhanced chemical vapor deposited vertical graphene arrays. (September 2022) - Sahoo, Surjit; Sahoo, Gopinath; Jeong, Sang Mun; Rout, Chandra Sekhar
Abstract: Vertical graphene (VG) or vertical graphene arrays have attracted the attention of researchers in recent years, as electrode materials for supercapacitor application due to its unique properties. Although significant progress has been made in growth and supercapacitor application of VG, still many recent developments not yet been reviewed. By attuning the growth of the graphene from horizontal to vertical, its electronic band structure and bandgap can be controlled which is evident from the theoretical and experimental findings. In VG electrolyte ions could smoothly transport through regions of one-dimensional structures and access the electroactive material's surface, and electrons can successfully move in the highly conductive VG to reach the current collector. Furthermore, high surface area can also accelerate other kinetic reactions and the one dimensional structure diminishes strain through volume expansion and contraction. These superiority make VG electrodes captivating in various future energy storage devices including lithium-ion batteries and supercapacitors. Herein, the importance of the structure, overview of various plasma enhanced chemical vapor deposition (PECVD) method of synthesis and the progress in bare and hybrid VG structures are reviewed. Afterward, the important strategies to enhance the energy storage performance by changing the morphology, surface engineering/functionalization and doping of VG are discussed. Furthermore, the challenges and future perspectives for achieving good structural quality with outstanding capacitance performance are listed. This review summarises the importance of vertical graphene structure, PECVD growth and mechanism of VG with recent progress and application towards efficient supercapacitor electrode material. Graphical abstract: Graphical illustration of the importance of growth, structure and morphology of plasma enhanced chemical vapor deposited vertical graphene arrays and their electrochemical energy storage performance. Unlabelled Image Highlights: Vertical graphene (VG) arrays have recently shown potential as electrodes for electrochemical double layer capacitors. Their peculiar characteristics like high conductivity, surface area, ion access facility and open structure are beneficial. The review article describes the plasma enhanced chemical vapor deposited VG for supercapacitor applications.